Bilateral facial nerve palsy in a patient with West Nile neuroinvasive disease - Nataša Nikolić; Ana Filipović; Nevena Todorović; Mirjana Jakšić Grgurović; Nikola Mitrović; Jovan Malinić; Ivana Milošević (Journal of Infection in Developing Countries)
Introduction: Bilateral facial nerve palsy (FNP) is a rare condition that is idiopathic in only 20%. FNP is the most common cranial neuropathy in West Nile neuroinvasive disease (WNND) but is usually unilateral and only a few cases of bilateral FNP have been reported.